Running with scissors : leading in uncertainty - Breen, Jennifer Moss; Abduljawad, Haytham; Font-Guzmán, Jacqueline N. (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
The more complex and ambiguous this world becomes, the greater the uncertainty leaders will face in their day to day professional and personal lives, and the greater the need to recognize and develop their leadership skills to help be the voice of reason when there's nothing around them but chaos.The book presents real case studies where the authors offer action learning methodologies grounded in various leadership theories. Whether you are a firm or skeptical believer in leadership development, the authors in this book, through their experiences and observations, illustrate how awareness, purpose, attitude, confidence, trust and mindset can play such a critical role in overcoming the toughest of circumstances.
Keywords: Leadership -- Cross-cultural studies.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books